2022
DOI: 10.7150/ijbs.70312
|View full text |Cite
|
Sign up to set email alerts
|

miR-199a-3p/5p regulate tumorgenesis via targeting Rheb in non-small cell lung cancer

Abstract: Lung cancer is one of the deadliest cancers, in which non-small cell lung cancer (NSCLC) accounting for 85% and has a low survival rate of 5 years. Dysregulation of microRNAs (miRNAs) can participate in tumor regulation and many major diseases. In this study, we found that miR-199a-3p/5p were down-expressed in NSCLC tissue samples, cell lines, and the patient sample database. MiR-199a-3p/5p overexpression could significantly suppress cell proliferation, migration ability and promote apoptosis. Through software… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
(46 reference statements)
0
8
0
Order By: Relevance
“…In addition, the increased expression level of miR-199a-5p could inhibit the proliferation of lung cancer cells and arrest the cell cycle in the G1 phase. In another of our research papers [ 37 ], we found that miR-199a-3p/5p were down-expressed in NSCLC tissue samples, cell lines, and the patient sample database. miR-199a-3p/5p overexpression could significantly suppress cell proliferation, migration ability and promote apoptosis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the increased expression level of miR-199a-5p could inhibit the proliferation of lung cancer cells and arrest the cell cycle in the G1 phase. In another of our research papers [ 37 ], we found that miR-199a-3p/5p were down-expressed in NSCLC tissue samples, cell lines, and the patient sample database. miR-199a-3p/5p overexpression could significantly suppress cell proliferation, migration ability and promote apoptosis.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the identified target genes of miR-199a may also be the targets of future drugs. For example, as mentioned above, our lab studies found that miR-199a-3p and miR-199a-5p could directly co-target Rheb (Ras homolog enriched in the brain) in lung cancer [ 37 ], regulating the mTOR signaling pathway, inhibiting cell proliferation, migration, and promoting cell apoptosis. The same is true for our laboratory’s discovery of MAP3K11 as a target gene for miR-199a-5p in NSCLC [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the above-mentioned miRNAs closely related to liver cancer, we selected miR-199a-3p, which was upregulated in the ATXP group vs. the model group and had the smallest differential expression, as the research object for follow-up experiments. miR-199a-3p had been identified in recent years as a promising diagnostic biomarker in a variety of malignancies, such as liver cancer, colorectal cancer ( 59 ), lung cancer ( 60 ), esophageal cancer ( 61 ), and ovarian cancer ( 62 ). The study found that miR-199a-3p was underexpressed in liver cancer, which was in line with our sequencing results.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-155-5p suppresses the migration and invasion of lung adenocarcinoma cells by targeting Smad2 [ 39 ]. MiR-199a-5p suppresses NSCLC progression [ 40 ], while miR-200b-3p and miR-9 promote NSCLC metastasis by targeting ABCA1 and TGFBR2, respectively [ 41 , 42 ]. In the study, most of the selected miRNAs were upregulated in the PD-L1-transfected cells.…”
Section: Discussionmentioning
confidence: 99%